1989
DOI: 10.1002/dev.420220807
|View full text |Cite
|
Sign up to set email alerts
|

Development of mother discrimination by single and multiple newborn lambs

Abstract: Most research on recognition of the ewe by her lamb has focused on lambs several days or even several weeks old, whereas newly born lambs have received little attention. The aim of this work was therefore to study the attraction of Merino lambs to postparturient ewes and their ability to discriminate between their own and alien mothers in a two-choice situation 12, 18, 24, 48, and 72 hr after birth. A comparison between singles and multiples was also made in 18 and 24-hr-old lambs. When released in the testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
1
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 24 publications
2
25
1
1
Order By: Relevance
“…The results obtained here in lambs with their intact mother are in agreement with previous reports (Nowak, 1990;Nowak & Lindsay, 1990;Nowak et al, 1987;Nowak et al, 1989;Terrazas, 1999) that lambs consistently discriminated between their own dam and an alien mother at ages varying from 12 to 24 hr. They also are consistent with the finding that at that early age, discrimination by the lamb occurs only at close quarters, with distal recognition becoming evident only several days later (Arnold, Boundy, Morgan, & Bartle, 1975;Nowak, 1990).…”
Section: Discussionsupporting
confidence: 93%
“…The results obtained here in lambs with their intact mother are in agreement with previous reports (Nowak, 1990;Nowak & Lindsay, 1990;Nowak et al, 1987;Nowak et al, 1989;Terrazas, 1999) that lambs consistently discriminated between their own dam and an alien mother at ages varying from 12 to 24 hr. They also are consistent with the finding that at that early age, discrimination by the lamb occurs only at close quarters, with distal recognition becoming evident only several days later (Arnold, Boundy, Morgan, & Bartle, 1975;Nowak, 1990).…”
Section: Discussionsupporting
confidence: 93%
“…The choice of the lamb during the preference test in Experiment 2 reflects a true learning process facilitated by colostrum ingestion or volumetric changes of the stomach. Because previous studies had consistently shown that discrimination occurs at close quarters (Nowak, 1991;Nowak et al, 1989), it was suggested that 24-hr-old lambs discriminate and prefer a mother that shows acceptance behaviors over a mother that shows rejection behaviors, and that the low-pitched bleats may be a determinant attractive element (Terrazas et al, 2002). In the present work, mothers emitted more low-pitched bleats and less high-pitched bleats than the alien ewes in all groups once the lambs were in the zone of contact.…”
Section: Discussionmentioning
confidence: 99%
“…Under such behavioral pressure, the young have patent advantages to recognize rapidly their own mother as she is the only care provider. Indeed, lambs discriminate their mother from alien ewes within 12 to 24 hr after birth (Nowak, Poindron, Le Neindre, & Putu, 1987;Nowak, Poindron, & Putu, 1989). Such an ability avoids rejection by alien ewes and optimizes the reunion with the dam at feeding times.…”
mentioning
confidence: 99%
“…It is therefore highly beneficial to the lamb to get rapidly attached to its dam. Most lambs can discriminate between their mother and an alien maternal ewe 12 to 24 h after birth [70,71] and this ability still improves markedly during the first few days postpartum [72]. While recognition of the mother at 24 h is based primarily on cues that lambs can perceive at close quarters, they can clearly discriminate their mother from a distance of several metres when 3 days old [73].…”
Section: Getting Attached To the Mothermentioning
confidence: 99%
“…While recognition of the mother at 24 h is based primarily on cues that lambs can perceive at close quarters, they can clearly discriminate their mother from a distance of several metres when 3 days old [73]. The development of early recognition of the dam varies according to breed, sex, and litter size [71,72]. Twins commonly take more than two days before they begin to show a preference for their dam.…”
Section: Getting Attached To the Mothermentioning
confidence: 99%